2018
DOI: 10.1007/978-3-030-03189-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in Resilient Organizations

Abstract: This chapter focuses on organizations' ability to change between different modes of operation as a key adaptive capacity that fosters resilience. Four modes are described which represent responses to low versus high demands on stability and flexibility respectively. The operational requirements for leaders both in enacting the different modes of operation and in instigating switches between the modes are detailed. Strategic recommendations are outlined that should help organizations to build the needed leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Perhaps some of the reason for the lack of research attention to regulation and management as potential sources of resilience is the critique of regulators and managers establishing too many rules, too much standardization, too much focus on resource allocation, and external control mechanisms for an adaptive system such as healthcare. 20 , 21 Instead of looking at regulation and management as being contradictory to resilience, 22 we argue that there is a need to discuss how we can stimulate resilience through regulation and management. Stimulating resilience can even be seen as central to changes in regulatory theory and practice that have evolved to more process-based types of regulation.…”
Section: Rethinking Safety In Healthcare Policy and Practice By Looking At Resiliencementioning
confidence: 99%
“…Perhaps some of the reason for the lack of research attention to regulation and management as potential sources of resilience is the critique of regulators and managers establishing too many rules, too much standardization, too much focus on resource allocation, and external control mechanisms for an adaptive system such as healthcare. 20 , 21 Instead of looking at regulation and management as being contradictory to resilience, 22 we argue that there is a need to discuss how we can stimulate resilience through regulation and management. Stimulating resilience can even be seen as central to changes in regulatory theory and practice that have evolved to more process-based types of regulation.…”
Section: Rethinking Safety In Healthcare Policy and Practice By Looking At Resiliencementioning
confidence: 99%
“…Transactional leadership “aimed at an exchange of rewards for fulfilling expectations” ( Grote, 2019, p. 60) seems necessary. Switching between fixed and flexible attitudes, and between different safety management modes of operation ( Pariès et al, 2019 ) are needed to restore society and economy after a disaster.…”
Section: Resultsmentioning
confidence: 99%
“…Simple, resilience implies the ability of a system to "bounce back" after disturbances and "bounce forward" by learning from those circumstances and enhance the adaptive ability of the system to handle surprises (Ilmola, 2016;Woods, 2015 andGrote, 2018). Surprises Resilience can improve safety institutions" capacity to deliberately deal with and react to complicated threats.…”
Section: Strategic Resiliencementioning
confidence: 99%
“…Previous research has tried to clarify the connection between strategic resilience and organizational culture significantly (Grote, 2018;Pettersen &Schulman, 2016 andCatalin &Mihaela, 2013). Evidence prior literature has shown that the ability to transform threats into possibilities, and the ability to take advantage of possibilities in a timely, non-crisis-like way, demonstrate strategic resilience.…”
Section: Strategic Resilience and Organisational Culturementioning
confidence: 99%